2016
DOI: 10.5194/bg-13-3647-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sporadic destratification, seasonal overturn, and artificial mixing on CH<sub>4</sub> emissions from a subtropical hydroelectric reservoir

Abstract: Abstract. Inland waters in general and freshwater reservoirs specifically are recognized as a source of CH4 into the atmosphere. Although the diffusion at the air–water interface is the most studied pathway, its spatial and temporal variations are poorly documented. We measured temperature and O2 and CH4 concentrations every 2 weeks for 3.5 years at nine stations in a subtropical monomictic reservoir which was flooded in 2008 (Nam Theun 2 Reservoir, Lao PDR). Based on these results, we quantified CH4 storage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…The dynamics of CO 2 in the NT2R is highly dependent on the hydrology and hydrodynamics of the reservoir as it has already been described for CH 4 (Guérin et al, 2016). During the warm seasons (WD and WW) when the water column is thermally stratified, the vertical profiles of CO 2 concentration in the water column are similar to profiles obtained in other tropical or subtropical reservoirs (Abril et al, 2005;Guérin et al, 2006;Chanudet et al, 2011;Kemenes et al, 2011), but also boreal reservoirs (Demarty et al, 2011). The high concentrations measured in the hypolimnion suggest that the main source of CO 2 is located at the bottom and very likely in the flooded soils, vegetation and sediments, whereas the decrease in CO 2 toward the surface suggest both consumption by primary production and/or loss to the atmosphere (Galy-Lacaux et al, 1997b;St Louis et al, 2000;Abril et al, 2005;Guérin et al, 2008;De Junet et al, 2009;Barros et al, 2011;Chanudet et al, 2011;Teodoru et al, 2011).…”
Section: Co 2 Dynamics In the Nt2r Water Column And Downstream Riverssupporting
confidence: 64%
See 2 more Smart Citations
“…The dynamics of CO 2 in the NT2R is highly dependent on the hydrology and hydrodynamics of the reservoir as it has already been described for CH 4 (Guérin et al, 2016). During the warm seasons (WD and WW) when the water column is thermally stratified, the vertical profiles of CO 2 concentration in the water column are similar to profiles obtained in other tropical or subtropical reservoirs (Abril et al, 2005;Guérin et al, 2006;Chanudet et al, 2011;Kemenes et al, 2011), but also boreal reservoirs (Demarty et al, 2011). The high concentrations measured in the hypolimnion suggest that the main source of CO 2 is located at the bottom and very likely in the flooded soils, vegetation and sediments, whereas the decrease in CO 2 toward the surface suggest both consumption by primary production and/or loss to the atmosphere (Galy-Lacaux et al, 1997b;St Louis et al, 2000;Abril et al, 2005;Guérin et al, 2008;De Junet et al, 2009;Barros et al, 2011;Chanudet et al, 2011;Teodoru et al, 2011).…”
Section: Co 2 Dynamics In the Nt2r Water Column And Downstream Riverssupporting
confidence: 64%
“…This assumption is reinforced by the fact that during the same sampling, hot moments of CH 4 emissions that should have occurred at the same time were captured (Guérin et al, 2016). As observed in most tropical and subtropical reservoirs, the higher concentrations were observed during the warm seasons due to long residence time of water and warmer conditions enhancing CO 2 build-up (Abril et al, 2005;Chanudet et al, 2011;Kemenes et al, 2011), whereas the lowest were found after reservoir overturn when the water outgassed (Chanudet et al, 2011). A significant shift in the carbon biogeochemical cycling occurred in the reservoir in 2013 with the reservoir water surface becoming a CO 2 sink during the WD season and the beginning of the WW season (from March to August).…”
Section: Co 2 Dynamics In the Nt2r Water Column And Downstream Riversmentioning
confidence: 90%
See 1 more Smart Citation
“…Methane emissions from fresh waters and estuaries occur through a number of pathways including (1) continuous or episodic diffusive flux across water surfaces, (2) ebullition flux from sediments, (3) flux mediated through the aerenchyma of emergent aquatic macrophytes (plant transport) in littoral environments, and also for reservoirs, (4) degassing of CH 4 in the turbines, and (5) elevated diffusive emissions in rivers downstream of the turbines especially if water through the turbines is supplied from anoxic CH 4 -rich water layers in the reservoir (Bastviken et al, 2004;Guérin et al, 2006Guérin et al, , 2016. It is very rare that complete emission budgets include all these types of fluxes.…”
Section: Other Inland Water Systems (Lakes Ponds Rivers Estuaries)mentioning
confidence: 99%
“…This is a transbasin hydroelectric reservoir that diverts water from the Nam Theun River (a Mekong tributary) to the Xe Bangfai River (another Mekong tributary). The reservoir was described in detail in Descloux et al (), and the carbon cycle and especially the greenhouse gas emissions were monitored since impoundment (Chanudet, Guédant, et al, ; Chanudet, Smits, et al, ; Deshmukh et al, , ; Guérin et al, ; Serça et al, ). The reservoir surface fluctuated from 140 km 2 (525.5 m above sea level) to around 490 km 2 at the full water level (538 m above sea level) between 2009 and 2013.…”
Section: Methodsmentioning
confidence: 99%